Balancing Innovation and Integrity: Navigating the Challenges of Generative AI in Higher Education - St. Clair, Norman S.; McCray, Pamela D. (International Journal of Advanced Corporate Learning (iJAC), 2026)
The rapid integration of Generative Artificial Intelligence (GAI) tools in higher education has sparked a myriad of discussions, presenting both remarkable opportunities and significant challenges. The problem lies in the dual nature of GAI: while it holds immense potential to enhance learning experiences, foster deeper engagement, and enable personalized education, its misuse for academic dishonesty raises profound concerns regarding the integrity of assessments and the authenticity of student work. The purpose of this paper is to explore the implications of GAI integration in higher education, focusing on the need to reimagine and reform assessment strategies, develop learning environments that promote the ethical use of AI, and implement institutional support systems to ensure that academic integrity remains intact. Our scope includes an examination of faculty perspectives on the pedagogical potential of GAI, the challenges of maintaining academic integrity, and innovative assessment strategies that can mitigate these risks. The central question addressed is how educators and institutions can balance the benefits of GAI with the need to uphold academic standards and integrity.